Endothelial dysfunction assessed by digital tonometry and discrepancy between fraction flow reserve and instantaneous wave free ratio. Issue 4 (3rd July 2020) - Jerabek, Stepan; Zemanek, David; Pudil, Jan; Bayerova, Kristyna; Kral, Ales; Kopriva, Karel; Kawase, Yoshiaki; Omori, Hiroyuki; Tanigaki, Toru; Chen, Zhi; Vodzinska, Alexandra; Branny, Marian; et al.
Abstract: Background: We tested whether the level of endothelial dysfunction assessed by digital tonometry, and expressed as reactive hyperemia index (RHI), is related to occurrences of a discrepancy between fractional flow reserve (FFR) and the instantaneous wave free ratio (iFR) (ClinicalTrials.gov identifier: NCT03033810). Methods: We examined patients with coronary stenosis in the range of 40–70%, assessed by both FFR and iFR (system Philips-Volcano) for stable angina. We included consecutive patients with FFR and iFR in one native coronary artery, and who had had no previous intervention. Results: We included 138 patients. Out of those, 24 patients (17.4%) had a negative FFR (with an FFR value >0.8) and positive iFR (with a iFR value ≤0.89) – designated the FFRn/iFRp discrepancy group, and 22 patients (15.9%) had a positive FFR (≤0.8) and negative iFR (>0.89) – designated the FFRp/iFRn discrepancy. RHI was higher in the discrepancy groups compared the group without discrepancy (1.73 ± 0.79 vs. 1.48 ± 0.50, p  = 0.025). However, this finding was not confirmed in multivariant logistic regression analyses. Patients with any type of discrepancy differed from the agreement group by having a higher occurrence of diabetes mellitus [9 patients (21.4%) vs. 36 patients (39.6%), p  = 0.029], active smoking (23 patients or 54.8% vs. 26 patients or 28.6%, p  = 0.003) and lower use of calcium channel blockers (9 patients, 21.4%, vs. 43 patients, 46.7%, p  = 0.004). Conclusion: The presence of endothelial dysfunction can be associated with a discrepancy in FFR/iFR. However, RHI correlated with risk factors of atherosclerosis, not with FFR or iFR.